Impacto da implantação de protocolo multidisciplinar de desmame da ventilação mecânica em unidade de terapia intensiva de hospital universitário brasileiro - Passos, Liliane Barbosa da Silva (2013)
Protocols of weaning from mechanical ventilation can improve patient outcomes, although results varied according to different populations. The aim of this study was to evaluate the impact of implementing a multidisciplinary protocol of weaning from mechanical ventilation in intensive care unit of a Brazilian university hospital. We conducted a prospective cohort before and after implementation of a protocol of weaning from mechanical ventilation in adult patients hospitalized in the unit, remained on mechanical ventilation for more than 24 hours and subjected to weaning from mechanical ventilation. We evaluated 96 patients before the implementation of the protocol and 139 patients after. In the first group, weaning was performed according to usual care and decision of physician. In the second group, used data in a systematic protocol and evaluated by a multidisciplinary team. Weaning from mechanical ventilation duration decreased from 6,8 to 3,6 days (p <0,001) and mortality in the intensive care unit from 14,6% to 7,2% (p: 0,03), with increased likelihood survival during hospitalization (p: 0,016) in the protocol group. Furthermore, the protocol was an independent predictor for discharge from the unit. However, it increased the unit stay (23,9 ± 18,5 x 18,6 ± 14,35 days, p: 0;009). We conclude that weaning from mechanical ventilation guided by a multidisciplinary protocol reduced mortality in the intensive care unit and length of mechanical ventilation weaning, but increased length of stay.